Anatomical selectivity in overlap of chronic facial and bodily pain. (May 2019) - Slade, Gary D.; Rosen, Jonathan D.; Ohrbach, Richard; Greenspan, Joel D.; Fillingim, Roger B.; Parisien, Marc; Khoury, Samar; Diatchenko, Luda; Maixner, William; Bair, Eric
Abstract: Background: Chronic facial pain often overlaps with pain experienced elsewhere in the body, although previous studies have focused on a few, selected pain conditions when assessing the degree of overlap. Aim: To quantify the degree of overlap between facial pain and pain reported at multiple locations throughout the body. Methods: Data were from a case–control study of US adults participating in the Orofacial Pain: Prospective Evaluation and Risk Assessment (OPPERA) project. They were interviewed to determine the presence of chronic facial pain (n = 424 cases) or its absence (n = 912 controls). A mailed questionnaire with a body drawing asked about pain at other locations. Odds ratios (ORs) and 95% confidence limits (95% CLs) quantified the degree of overlap between facial pain and pain at other locations. For replication, cross-sectional data were analyzed from the UK Biobank study (n = 459, 604 participants) and the US National Health Interview Survey (n = 27, 731 participants). Results: In univariate analysis, facial pain had greatest overlap with headache (OR = 14.2, 95% CL = 9.7–20.8) followed by neck pain (OR = 8.5, 95% CL = 6.5–11.0), whereas overlap decreased substantially (ORs of 4.4 or less) for pain at successively remote locations below the neck. The same anatomically based ranking of ORs persisted in multivariable analysis that adjusted for demographics and risk factors for facial pain. Findings were replicated in the UK Biobank study and the US National Health Interview Survey. The observed anatomical selectivity in the degree of overlap could be a consequence of neurosensory and/or affective processes that differentially amplify pain according to its location. Abstract : Supplemental Digital Content is Available in the Text.